Isolation, Characterization, and Genomic Analysis of Bacteriophages Against Pseudomonas aeruginosa Clinical Isolates from Early and Chronic Cystic Fibrosis Patients for Potential Phage Therapy - Hanzada T. Nour El-Din; Maryam Kettal; José C. Granados Maciel; Greg Beaudoin; Umut Oktay; Sabahudin Hrapovic; Subash Sad; Jonathan J. Dennis; Danielle L. Peters; Wangxue Chen (Microorganisms)
Pseudomonas aeruginosa is associated with both community and hospital-acquired infections. It colonizes the lungs of cystic fibrosis (CF) patients, establishing an ecological niche where it adapts and evolves from early to chronic stages, resulting in deteriorating lung function and frequent exacerbations. With antibiotics resistance on the rise, there is a pressing need for alternative personalized treatments (such as bacteriophage therapy) to combat P. aeruginosa infections. In this study, we aimed to isolate and characterize phages targeting both early and chronic P. aeruginosa isolates and evaluate their potential for phage therapy. Four highly virulent phages belonging to myoviral, podviral, and siphoviral morphotypes were isolated from sewage samples. These phages have a broad host range and effectively target 62.5% of the P. aeruginosa isolates with a positive correlation to the early isolates. All the phages have a virulence index of ≥0.90 (0.90–0.98), and one has a large burst size of 331 PFU/cell and a latency period of 30 min. All phages are stable under a wide range of temperature and pH conditions. Genomic analysis suggests the four phages are strictly lytic and devoid of identifiable temperate phage repressors and genes associated with antibiotic resistance and virulence. More significantly, two of the phages significantly delayed the onset of larval death when evaluated in a lethal Galleria mellonella infection model, suggesting their promise as phage therapy candidates for P. aeruginosa infections.